1995
DOI: 10.1302/0301-620x.77b2.7706335
|View full text |Cite
|
Sign up to set email alerts
|

A cadaver study of the function of the oblique part of vastus medialis

Abstract: Six normal cadaver lower limbs were mounted on a specially designed loading apparatus. Wires were used to simulate the five muscle bellies of the quadriceps, the ratio of their tensions having been determined from that of the anatomical cross-sectional areas of the muscles. A three-camera system was used to track the patella during knee movements from flexion to extension. The patellofemoral contact area was determined by pressure-sensitive film. The limb was loaded with and without tension on the wire which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
120
4
7

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 8 publications
8
120
4
7
Order By: Relevance
“…This in vitro experiment confirmed the general pattern of patellar kinematics found in some previous studies, 13,14,20,22,39 with the patella translating medially as the knee starts to flex, then translating progressively laterally from 208 to 908 knee flexion. The kinematic pattern was repeatable between knees and the medial-lateral translation pattern matched data from dynamic measurements obtained previously in vivo.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This in vitro experiment confirmed the general pattern of patellar kinematics found in some previous studies, 13,14,20,22,39 with the patella translating medially as the knee starts to flex, then translating progressively laterally from 208 to 908 knee flexion. The kinematic pattern was repeatable between knees and the medial-lateral translation pattern matched data from dynamic measurements obtained previously in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…37,38 This clinical knowledge suggests the importance of having experimental tracking data that are based on the physiological/anatomical tensions and orientations of all the quadriceps muscle components, 25 especially the VMO. 39 One important factor in achieving realism was that we measured patellar tracking during knee flexion-extension motion cycles. Some studies have reported ''kinematics'' based on a sequence of measurements in static postures, so may have failed to record transient effects.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the fiber orientation in the distal part of the muscle is noticeably more horizontal than in the proximal part, and there is considerable evidence the distal part has a role in maintaining patellar alignment [24]. The distal part, which can be considered the functional equivalent of the VMO, has its own motor point, is a relatively weak extensor, inserts into the medial border of the patella [23], is more active at 90°fl exion than the rest of quadriceps [22], and pulls the patella medially [15,17,25]. Although Peeler et al [31] said there was no sign of a separate nerve entering the VMO, numerous authors disagree [16,17,20,41,44].…”
Section: Discussionmentioning
confidence: 99%
“…Various different techniques for doing this are described in the literature: Sakai et al [24] digitised two points on a medial-lateral axis (not described in full), a third point on the proximal pole, and the centre of the patella. Several authors digitised the medial-lateral axis and proximal-distal axis by the most prominent proximal/medial/distal/lateral points on the patella [7,9,23]. Being points located through the skin, these have an indirect relationship to the articular geometry, which must be further quantified if contact conditions are of interest.…”
Section: Patellar Body-fixed Axesmentioning
confidence: 99%